Pahanhautoja = Hatching [videorecording (DVD)] - Rautsi, Ilja; Heikkila, Sophia; Solalinna, Siiri; Volanen, Jani, 1971- (IFC Films, 2022)
Twelve-year-old Tinja is desperate to please her mother, a woman obsessed with presenting the image of a perfect family. One night, Tinja finds a strange egg. What hatches is beyond belief.